Optimizing Funding Sources to Improve Education Quality in the Digital Era - Holilur Rahman; Fariyah, Fariyah; Siti Wasilah; Amani Bariroh; Ririn Sri Kustinah (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
This study aims to describe strategies for optimizing educational funding sources through digitalization of financial governance and analyze the obstacles faced by schools in its implementation. The digital era presents both opportunities and challenges for educational institutions in optimizing funding sources to improve educational quality. School financial management now relies not only on government funds but also demands innovation, transparency, and the use of digital technology. This study uses a descriptive qualitative approach with a review of relevant literature on educational funding management, school financial digitalization such as ARKAS, SIPLah, and e-RKAS, as well as supporting and inhibiting factors for implementation. The results of the discussion indicate that digitalization can increase transparency, accountability, and effectiveness of fund management, although obstacles remain such as limited internet access, ICT facilities, and low digital literacy among education personnel, especially in 3T areas. Optimization of funding can be achieved through diversifying funding sources, strengthening human resource capacity, utilizing digital technology, and collaborating with the community and external institutions. With the right strategy, schools can improve educational quality sustainably and adapt to developments in the digital era.